Transcriptomic profile of cystic fibrosis airway epithelial cells undergoing repair - Zoso, Alice (Sci Data, 2019)
Pathological remodeling of the airway epithelium is commonly observed in Cystic Fibrosis (CF). The different cell types that constitute the airway epithelium are regenerated upon injury to restore integrity and maintenance of the epithelium barrier function. The molecular signature of tissue repair in CF airway epithelial cells has, however, not well been investigated in primary cultures. We therefore collected RNA-seq data from well-differentiated primary cultures of bronchial human airway epithelial cells (HAECs) of CF (F508del/F508del) and non-CF (NCF) origins before and after mechanical wounding, exposed or not to flagellin. We identified the expression changes with time of repair of genes, the products of which are markers of the different cell types that constitute the airway epithelium (basal, suprabasal, intermediate, secretory, goblet and ciliated cells as well as ionocytes). Researchers in the CF field may benefit from this transcriptomic profile, which covers the initial steps of wound repair and revealed differences in this process between CF and NCF cultures.